Alleviation of Soil Acidity by Application of Compost for Grain Maize Production - Sahar Yusuf, Enita (2002)
Returning organic materials in the form of compost can be an alternative method of alleviating soil acidity. This is because decomposted organic materials help chelate AI, thereby reducing its toxicity to crop. A set of three experiments was conducted in a glasshouse at UPM. The first experiment was the used of inoculant and activator in composting. This experiment was to evaluate the effectiveness of different type of inoculants as decomposters. The second experiment was a pot experiment using grain maize variety PJ-58 as a test crop to determine the best compost. The soil type was the Bungor series soil (Typic Paleudult). The third experiment (also pot experiment) was to grow grain maize on the Bungor and Kuantan series soils in order to evaluate the effectiveness of compost as a soil ameliorant. The results indicated that during compo sting the temperature of the compost increased up to > 60˚C. This showed that effective microorganisms (EM) is a good inoculant to decompose palm oil mill effluent. It was found that compost application had alleviated soil acidity. Applying compost at the rate of 20 t1ha plus 2 t GML/ha increased soil pH from 4.6 to 5.7. The exchangeable K, Ca and Mg had also increased. This treatment gave the best result. For the Bungor series soil, the critical Ca concentration in the tissue was 0.65 %, while the critical Mg concentration it was 0.42 %. The critical exchangeable Ca concentration was 2.7 cmol/kg soil. The best compost was compost type 2 (CT2) where EM as an inoculant while urea and rice branch as an activator was applied. Its application to the soil gave the high exchangeable Ca and Mg, soil cation exchange capacity and the lowest exchangeable AI. It also gave the highest maize dry weight. It was noted that compost application had improved soil fertility leading to increase in grain maize yield.